Lithuanians in Nazi Concentration Camps, 1941–1945 - Rudokas, Dominykas (Genocidas ir rezistencija, 2026)
This article applies a critical analysis approach to examine the imprisonment of Lithuanians in Nazi camps between 1941 and 1945 and to systematise the key historical features of these camps. In 1943–1944, Lithuanians were primarily interned as political prisoners, though some also ended up in the camps for criminal offences (illegal activities, sabotage of requisitions) or for asocial behaviour (alcoholism, prostitution, unemployment). Political prisoners were usually held in Stutthof, whereas other camps had more prisoners detained for other reasons. At Ravensbrück, for example, Lithuanian women were imprisoned for asocial behaviour. The number of Lithuanian prisoners in Nazi camps generally ranged from 200 to 300, with the exception of Majdanek (1,000), Stutthof (1,200) and Flossenbürg (2,500); mortality rates were no lower than 90%, and it is still unknown how many people perished during the so-called death marches. Between 1933 and 1945, the Nazi concentration camp system underwent significant changes, directly shaped by the regime’s objectives and policies. Lithuanians encountered this system at a time when its internal regulatory structures had already been formed, yet the expansion of the camp system was extremely rapid, mortality had reached its highest level, and the camps themselves had become the main sites in the Nazi system of forced labour and extermination.
Keywords: Lithuania; Nazi occupation; repression; concentration camps